Gambaran peresepan obat antiepilepsi pada pasien rawat jalan di Rumah Sakit Jiwa Prof. Dr. Soerojo Magelang periode Januari – Juni 2022 - Sari, Dela Puspita; Agusta, Herma Fanani; Yuliastuti, Fitriana (Universitas Muhammadiyah Magelang, 2024)
Epilepsy is one of the most important neurological diseases. Epilepsy is often associated with physical injury, mental injury, and severe psychosocial consequences for those affected. The study aims to determine the description of anti-epileptic drug prescribing for outpatients at Prof. Dr. Soerojo Magelang Mental Hospital in January-June 2022. The method used in this research was descriptive, and it took saturated samples in the form of prescriptions from patients who met the inclusion criteria with an age range of 18-40 years. The results of the study showed that the sufferers who received the most antiepileptic drugs were women aged 18-29 years. The average number of drug items per prescription sheet is 1.99 following WHO standards. The most commonly prescribed antiepileptic drug is a single carbamazepine (20.49%), followed by a combination of Carbamazepine with Divalproex Sodium (13.66%) and a combination of Carbamazepine, Clobazam and Divalproex Sodium (12.68%). In contrast, the most common dosage and rules for use of antiepileptic drugs are Clobazam 1mg tablet, dose once a day, 1 tablet (20.78%).